Main scales used in an intensive care unit for pressure injuries: An integrative review (Research, Society and Development, 2022)
Considering the incidence and severity of the occurrence of pressure injuries and the critical clinical condition of the patient in the intensive care unit, the present study was developed with the objective of identifying the main scales used for the prevention, evaluation and treatment of PI in the care unit intensive. The methodology used for the elaboration of this work was an integrative literature review. This type of research is a clear and reproducible methodology, and it is a specific method that provides a more comprehensive view of a given topic. An acronym PECO was formulated for the elaboration of the guiding question of the research: Which scales are used for the prevention, evaluation and treatment of pressure injuries in an intensive care unit? In the second phase, a search was carried out in the literature, in the PubMed and BvS (Virtual Health Library) databases. Through the following search strategy: Intensive Care Units AND Pressure Injury AND Scale, where 259 articles were found. Of these, 21 articles were selected for final reading, and 14 selected articles were used in the study. Inclusion criteria were: articles published in the last 10 years, articles in Portuguese/English and online access to the full abstract. It was observed that the Braden scale is one of the most used resources in ICUs to measure the risk of critically ill patients to develop pressure injuries. Based on this record, nurses are able to apply preventive measures and promote effective treatment.